Pemberian Minuman Jahe dan Madu Terhadap Mual Muntah Pada Ibu Hamil Trimester I - Setiyaningsih, Fera Yuli; Isro'aini, Any (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2023)
Nausea and vomiting begin in the 1st trimester around 6-8 weeks of gestation, peak at nine weeks of gestation and persist around 12 weeks. A small number of pregnant women still feel nausea and vomiting at 20 weeks of gestation. Approximately 50 – 80% of pregnant women experience this discomfort, and around 50% - 90% of pregnant women experience nausea and vomiting during 1st trimester. The purpose of this study was to determine the effect of giving ginger and honey on nausea and vomiting in 1st trimester-pregnant women in MombyKids Jombang. The research design used the One-Group Pretest-Posttest Design. The research subjects were first-trimester pregnant women who checked their pregnancy at MombyKids Jombang. Data analysis used the Wilcoxon test. The results of the study showed that there was an effect of giving ginger on nausea and vomiting, the frequency of nausea and vomiting before giving ginger and honey in the 1st trimester of pregnant women. The conclusion in this study was that in the 1st trimester pregnant women who consumed ginger and honey the frequency of nausea and vomiting was reduced compared to the 1st trimester pregnant women who did not consume ginger and honey. The pregnant woman suggested using ginger and honey as non-pharmacological therapy, but continued the research by increasing the number of samples should be followed to strengthen this finding.